Close-proximity tidal phasing for 'firm' electricity supply. (March 2017) - Commin, Andrew N.; McClatchey, John; Davidson, Magnus W.H.; Gibb, Stuart W.
Abstract: Tidal generation is highly predictable and thus an attractive renewable energy source to develop; however, output varies over short time scales. This can be mitigated through phasing of output between sites, as different locations have different timings of output. Phasing can be increased by geographical diversity; unfortunately areas with tidal resources suitable for generation are few, so the opportunity for this is limited. The Pentland Firth and Orkney Waters (PFOW) contain the World's first leased sites for tidal stream generation. This paper focuses on close-proximity phasing between these leases and their ability to provide firm power, i.e. a guaranteed level of output. Results show phasing across individual leases and over the PFOW; combined output from all the lease areas exceeds 1% of nameplate capacity for 97.9% of the study, compared to 83.4%–94.5% for the individual leases. Relatively little storage makes significant levels of firm capacity obtainable; 255 MWh of storage means electricity demand of the two counties the developments fall within would be met ∼94% of the time. The methodology identifies lease suitability, high energy locations within leases, and quantifies the complementary characteristics of different tidal sites. This could inform strategic development of tidal sites, to maximise firm capacity. Highlights: There is substantial sub-hourly tidal phasing within Pentland Fith and Orkney Waters. 5% firm capacity only requires 34 MWh of storage per 100 MW of installed generation. Firm capacity from phasing is limited to ∼10% due to the spring/neap cycle.